2016
DOI: 10.3892/or.2016.5100
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin induces cell apoptosis in Mia PaCa-2 cells via the suppression of nuclear factor-κB and activation of ERK and JNK: A novel therapeutic implication for pancreatic cancer

Abstract: Melatonin is synthesized by the pineal gland and is released into the blood. In the last several years, some studies have shown that melatonin has anticancer properties; however, the mechanisms behind the antitumour traits are unclear, especially in pancreatic cancer. Therefore, in the present study, we investigated the antitumour effects of melatonin on the human pancreatic carcinoma cell line MIA PaCa‑2 and explored its biological mechanisms. MIA PaCa‑2 cells were treated with melatonin, and we used a CCK‑8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…NF-κB induces the expression of Snail (20), ZEB-1 and ZEB2 (21) to promote EMT and cancer metastasis. It was also previously demonstrated that melatonin potently inhibits the activity of NF-κB (22). In the present study, EMSA analysis confirmed that IL-1β enhanced NF-κB transcriptional activity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…NF-κB induces the expression of Snail (20), ZEB-1 and ZEB2 (21) to promote EMT and cancer metastasis. It was also previously demonstrated that melatonin potently inhibits the activity of NF-κB (22). In the present study, EMSA analysis confirmed that IL-1β enhanced NF-κB transcriptional activity.…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported that NF-κB inhibits the expression of E-cadherin and desmoplakin and induces the expression of vimentin by promoting the expression of Snail (20), ZEB-1 and ZEB-2 (21), thereby initiating EMT. Other studies have demonstrated that melatonin exerts an inhibitory effect on NF-κB (22). However, to the best of our knowledge, there is currently no study investiagting these pathways in Gc.…”
Section: Introductionmentioning
confidence: 89%
“…However, the activation of executor of apoptosis (caspase-3) and DNA fragmentation have not been observed, indicating that the apoptotic process might not be completed [43,87,88]. The pro-apoptotic effect of melatonin on pancreatic tumor cells has been demonstrated by Li et al and Xu et al, who have shown that the application of melatonin to cancer cells resulted in the strong expression of pro-apoptotic Bax proteins followed by the activation of caspase-3 and inhibition of an anti-apoptotic protein Bcl-2 [82,89]. Similar results have been demonstrated in the pancreatic AR42J tumor acinar cells.…”
Section: Melatonin System and Pancreatic Cancermentioning
confidence: 99%
“…According to the data of Li et al [89], melatonin inhibited cell viability, suppressed colony formation, reduced cell migration and invasion, and induced cell apoptosis in pancreatic carcinoma cells. In addition, recent studies have shown that high doses (mM) of melatonin decreased pancreatic tumor cells proliferation and invasion by inhibition of NF-κB signaling pathway, but also enhanced gemcitabine cytotoxicity in these cells [100].…”
Section: Melatonin System and Pancreatic Cancermentioning
confidence: 99%
“…Plenty of studies have shown that melatonin and its metabolites can serve as broad-spectrum antioxidants and free radical scavengers [26][27][28] . They can potentially regulate the process of apoptosis and inflammation in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%